Improving Students’ Character of Caring for The Environment Through Understanding Ecoliteracy in Picture Stories - Samsudin; Cahyono, Hadi Cahyono; Sunarto (AT-TAJDID: Journal of Islamic Education, 2025)
Environmental problems caused by human or natural factors are increasing. These natural disasters will get worse if prevention is not done early. Efforts to reduce disasters that occur are to instill the character of caring for the environment from an early age. The way to introduce character education to children is through the storytelling method. The storytelling method is a program or plan that can be used in order to introduce care for the natural environment through the plot, moral messages and emotions of the story told to children. A child who has concern for the environment will have a positive effect on the survival of the surrounding environment and last until he grows up, because it becomes a habit. This research uses the literature research method. The source of reading material used is obtained from other people's research that has been published in the form of books, journals and in the form of articles that can be found in the library. Researchers study literature, writings and sources that have a close relationship regarding the problem being studied, namely about strengthening the character of environmental care in early childhood.